Determinants of investment attractiveness of countries and investment climate assessment methods. Survey analysis - Piotr Misztal; Vasili Kulakov (Journal of Modern Science)
Objectives The purpose of the research is the identification of important determinants shaping the investment attractiveness of the country from the point of view of potential investors and assessment the degree of stakeholder satisfaction with existing methods of examining the investment climate and their availability for practical use.